2008
DOI: 10.1271/bbb.70600
|View full text |Cite
|
Sign up to set email alerts
|

Purification and N-Terminal Amino Acid Sequence of Solanapyrone Synthase, A Natural Diels-Alderase fromAlternaria solani

Abstract: The first natural Diels-Alderase, solanapyrone synthase, was purified 1,630-fold from a crude extract. The 41-kDa protein on SDS-polyacrylamide gel electrophoresis was identified as truncated solanapyrone synthase, and its N-terminal amino acid sequence was found to be QETQNLNNFLESNAINP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The sol5 gene encodes a polypeptide of 515 amino acid‐long polypeptide, which was considered to be SPS, an enzyme responsible for the Diels–Alder cycloaddition in solanapyrone biosynthesis. The presence in its N terminus of a signal peptide of 20 amino acids for secretion was predicted by the SignalIP server25 and the sequence following after the 25th amino acid was identical with that found in the partially purified SPS 19. A conserved domain search indicated the presence of a flavin‐binding domain (Pro95 to Ser230) in which the His128 residue was suggested as a site of covalent flavinylation (Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The sol5 gene encodes a polypeptide of 515 amino acid‐long polypeptide, which was considered to be SPS, an enzyme responsible for the Diels–Alder cycloaddition in solanapyrone biosynthesis. The presence in its N terminus of a signal peptide of 20 amino acids for secretion was predicted by the SignalIP server25 and the sequence following after the 25th amino acid was identical with that found in the partially purified SPS 19. A conserved domain search indicated the presence of a flavin‐binding domain (Pro95 to Ser230) in which the His128 residue was suggested as a site of covalent flavinylation (Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 80%
“…Although SPS was not fully purified, its oxidase activity could not be decoupled from the cycloaddition activity, and so SPS was considered to be an oxidase converting 2 into 3 , which is then cyclized and released as 1 18. Recently, Katayama et al reported that a more than 1630‐fold purification of SPS from a crude extract of A. solani was not sufficient to obtain a homogeneous SPS preparation, due to its instability and degradation by contaminating proteases 19…”
Section: Introductionmentioning
confidence: 99%
“…102,106 Sol5 (solanapyrone synthase) also appears to accelerate the intramolecular [4 + 2]-cycloaddition of 42 to produce a mixture of solanapyrone A ( 43 ) and solanapyrone D ( 45 ). 33,95,102,106,107 In the final step of the pathway, the dehydrogenase Sol3 reduces the aldehyde functionality of 43 and 45 to provide 44 and 46 , respectively. 102 …”
Section: Solanapyrone Synthasementioning
confidence: 99%
“…Using crude enzyme, we found that both 13 and 14 were converted into 15 and 16 [6]. Although purification of solanapyrone synthase (SPS) was hampered by its instability, it has been purified as a single band on SDS-PAGE (sodium dodecyl sulfate polyacrylamide gel electrophoresis) [26]. Recently, the gene cluster responsible for biosynthesis of solanapyrones has been identified by homology based PCR (polymerase chain reaction) and genome walking [27].…”
Section: Macrophomate Synthasementioning
confidence: 99%